Developing Applications using Spatial Data Infrastructure GeoServices. Use Cases: Directorio Comercial SC, AgroMAG, IDEHN Mobile - Víquez-Acuña, Óscar (2017)
A Geographic Data Infrastructure (GDI) allow users to manage and publish geographic data representing national, regional and local information from several nodes. These nodes can establish a GDI network if the information they contain is related to each other. In this context, the Geographical Data Infrastructure for the Huetar Norte región (IDEHN) was created to publish regional information from various sources.To consult this information, IDEHN makes available geoservices to get remote Access to the data from geoportals, geographical information systems tools and specific desktop software or mobile devices apps.Over this workspace, this article presents three software examples of using IDEHN geoservices to Access geographical information in mobile devices.